Fourth Five Year Plan 1969-74 Draft Proposals - Government of Haryana (Government of Haryana, 1974)
The Fourth Five Year Plan Draft Proposals for Haryana (1969–74) presents a detailed physico-geographical survey of the newly formed state, which, as of April 1969, covered an area of 43,869 sq. km with a projected population of 9.9 million. Bounded by the Shivalik range to the north, the Yamuna River to the east, the Aravalli ranges and Bikaner desert to the south-west, and the Ghaggar stream to the west, Haryana’s landscape is predominantly a plain at an average elevation of 927 feet, interspersed with sand dunes, the Sohna plateau, and the Aravalli ranges. The Morni Hills in Ambala district form the state’s highest point at 4,919 feet, while Pinjore Gardens stand at 2,217 feet. The state is distant from perennial rivers like Ravi, Beas, and Sutlej, with the Yamuna providing limited irrigation in the south-east and the Ghaggar river flowing in some areas. Annual rainfall varies significantly across districts, ranging from 39.82 cm in Hissar to 97.45 cm in Ambala. The state’s soils are predominantly alluvial, classified into five types: desert soils, sierozem soils, arid brown soils, tropical arid brown soils, and reddish chestnut soils, each with varying fertility, nutrient deficiencies, and susceptibility to water and wind erosion. Water resources are unevenly distributed, with sweet water belts concentrated in Ambala, Karnal, parts of Gurgaon, Mahendragarh, Rohtak, and Hissar, while much of western Haryana faces deep or brackish sub-soil water, complicating irrigation. The water-table depth further divides the state into regions of more than 30 feet and 5–30 feet. Overall, Haryana exhibits a diverse terrain and soil profile, presenting both opportunities and challenges for agricultural development, irrigation planning, and natural resource management under the Fourth Five Year Plan.
Government of Haryana Planning Department 1968
Government of Haryana Planning Department 1968
Keywords: Haryana; State Plan; Physico-Geographical Conditions; Soil Types; Water Resources; Rainfall; Aravalli Ranges; Morni Hills; Desert Soils; Irrigation; Sub-Soil Water; Agriculture